Trend of career counseling: bibliometric analysis and literature review - Febriyani, Tika; Iqbal; Al-falathi, Siti Aminah; Prabowo, Arga Satrio (Universitas Islam Negeri Raden Intan Lampung, 2025)
In Indonesia, tight labor competition and high unemployment rates among graduates are reasons for the need for effective and thorough career preparation. This research uses bibliometric analysis to provide graphic information about the statistical overview of literature from 380 articles published in reputable international journals that correlate with career counseling from 2009 to 2023. An in-depth study was carried out on 371 articles to reveal this research. Types of documents from the Scopus database for career counseling for students are articles, books, reference books, and conference papers. Visualization with R software bibliometrics with three visuals: annual scientific production, most cited articles, country scientific production, and word cloud and co-occurrence network. The analysis findings show that career counseling is the dominant topic. Research topics for 2009-2023 are humans, women, men, and adults. Less researched topics are decision-making, counseling, students, and young adults. This study can provide a global roadmap for researchers regarding career counseling.